Comparison of de novo IgM and IgG anti‐HLA DSAs between belatacept‐ and calcineurin‐treated patients: An analysis of the BENEFIT and BENEFIT‐EXT trial cohorts. Issue 9 (16th June 2018) - Everly, Matthew J.; Roberts, Mustimbo; Townsend, Robert; Bray, Robert A.; Gebel, Howard M.
Abstract : Preventing conversion of donor‐specific anti‐HLA antibodies (DSAs) from an IgM‐to‐IgG could a way to prevent chronic rejection. We evaluated whether belatacept‐treated patients (belatacept less‐intensive [LI] or more‐intensive [MI] regimens) have a lower rate of conversion than do cyclosporine A (CsA)–treated patients. We included 330 HLA‐mismatched patients from 2 phase 3 trials with either (a) complete donor/recipient HLA‐A, ‐B, ‐DR, and ‐ DQ loci typing or (b) incomplete HLA typing with IgG DSAs detected pretransplant or posttransplant. IgM and IgG DSAs were tested with single antigen beads at 0, 6, 12, 24, and 36 months posttransplant. The overall (preexisting or de novo) rates of IgM‐ and IgG‐positive DSAs were 29% and 34%, respectively. The pretransplant IgM and IgG DSA‐positive frequencies were similar between treatment groups. The IgG‐positive dnDSA rate was significantly higher in the CsA‐treated group (34%) compared with the belatacept‐LI (8%) and belatacept‐MI (11%) ( P  < .001) groups. In IgM‐positive dnDSA patients, the IgG‐positive dnDSA rate of conversion was 2.8 times higher in the CsA group than in the combined belatacept groups ( P  = .006). However, the observed association between belatacept treatment and more limited conversion of IgM‐to‐IgG dnDSAs was based on a limited number of patients and requires further validation. Abstract : Posttransplant immunosuppression with belatacept may provide superior prevention of IgM to IgG donor‐specific antibody conversion compared to cyclosporine.